2022
DOI: 10.3390/ijms232012418
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Primary Carbon Metabolism in Cucumber Infected with Pseudomonas syringae pv lachrymans: Local and Systemic Responses

Abstract: The reconfiguration of the primary metabolism is essential in plant–pathogen interactions. We compared the local metabolic responses of cucumber leaves inoculated with Pseudomonas syringae pv lachrymans (Psl) with those in non-inoculated systemic leaves, by examining the changes in the nicotinamide adenine dinucleotides pools, the concentration of soluble carbohydrates and activities/gene expression of carbohydrate metabolism-related enzymes, the expression of photosynthesis-related genes, and the tricarboxyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…The content of nicotinamide adenine dinucleotides was determined using enzyme cycling assays, employing 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT) as the terminal electron acceptor, with phenazine methosulfate (PMS) serving as an electron carrier. The reaction was based on either the conversion of EtOH to acetaldehyde, catalyzed by alcohol dehydrogenase (ADH, EC 1.1.1.1) for NAD(H) determination, or the conversion of glucose-6-phosphate (G6P) to 6-phosphogluconolactone by glucose-6-phosphate dehydrogenase (G6PDH, EC 1.1.1.49) for NADP(H) determination [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The content of nicotinamide adenine dinucleotides was determined using enzyme cycling assays, employing 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT) as the terminal electron acceptor, with phenazine methosulfate (PMS) serving as an electron carrier. The reaction was based on either the conversion of EtOH to acetaldehyde, catalyzed by alcohol dehydrogenase (ADH, EC 1.1.1.1) for NAD(H) determination, or the conversion of glucose-6-phosphate (G6P) to 6-phosphogluconolactone by glucose-6-phosphate dehydrogenase (G6PDH, EC 1.1.1.49) for NADP(H) determination [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sugars and their metabolism contribute to a plant's immunity as they are associated with increasing cell wall lignification, oxidative burst, the stimulation of flavonoid synthesis (sucrose), and some PR protein expression (by glucose) [71,100]. It has also been suggested that a lowered hexose/sucrose ratio during infection can trigger PR gene expression [102]. Infection forces plants to undergo carbon nutrient mobilization, accompanied by photosynthesis reduction, increased respiration, and alterations in nitrogen and lipid metabolism.…”
Section: Changes In Polar Metabolic Profiles Of Pea Seedlings After I...mentioning
confidence: 99%
“…Soluble carbohydrates are synthesised, for example, in response to osmotic stress, protecting cellular members and improving survival under stress conditions [ 29 ]. Biotic elicitors, such as pathogen infection, also produce changes in the distribution and metabolism of carbohydrates in plants [ 30 ]. Red plus blue LEDs [ 31 ] stimulate carbohydrate biosynthesis in vitro in Doritaenopsis plants, as does white LED light in N .…”
Section: Introductionmentioning
confidence: 99%